IMPLEMENTASI KEBIJAKAN PROGRAM PENERAPAN TEKNOLOGI PERTANIAN DI KECAMATAN BANGKO KABUPATEN ROKAN HILIR TAHUN 2018-2020 - Santoso, Bulyah; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Agricultural Technology Application Program is one of the program policies of the Department of Food and Agriculture Security of Rokan Hilir Regency which aims to provide agricultural facilities and infrastructure to increase agricultural productivity in increasing self-sufficiency in agriculture. The problem in this research is that the implementation of the Agricultural Technology Program Policy has not been maximized due to several factors that support the performance of the policy implementation not being achieved. The purpose of this study was to determine the Implementation of Agricultural Technology Application Program Policies in the District of Parit Aman in Bangko District, Rokan Hilir Regency in 2018-2020. The approach used in this study is a qualitative approach. This type of research is descriptive. There are two types of data in this study, namely primary data and secondary data. Data collection techniques using interviews, observations and documentation as well as data analysis techniques in this study were qualitative. The result of this study is that the implementation of the Agricultural Technology Application Program Policy in the Penghuluan Parit Aman District, Bangko District, Rokan Hilir Regency in 2018-2020 has not been optimal, this is because there are several important dimensions that affect the performance of policy implementation that has not run optimally, namely the dimensions of resources and communication between organization. Key word : Implementation, Policy, Agricultural Program